Maksim Gorky’s Reading of Aleksandr Pushkin (Based on the Drama The Lower Depths) - Kunarev, Andrei (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2024)
The significant influence of Pushkin on the formation of Maksim Gorky as an artist is an undeniable fact. Nevertheless, the problem of Gorky’s reception of Pushkin’s heritage has not been sufficiently investigated. The question of Pushkin’s presence in the drama “The Lower Depths” has not been raised at all, although examination of the seemingly well-studied text of the play allows us not only to re-evaluate its originality, but also to reveal important semantic nuances. The subject of this publication, which opens a series of articles devoted to the study of the peculiarities of Gorky’s mastering of Pushkin’s work based on the drama “The Lower Depths”, is the remark of the Actor, who, quoting Pushkin’s ballad “The Drowned Man” (1828), attributes its authorship to Béranger. This article attempts to clarify some aspects of the study of the ballad “The Drowned Man” and the poem <Refutation of Mr. Béranger> (1827) by Pushkin.